Micromechanical progressive damage model for predicting resin dominated strength values of fibre reinforced composite under various types of loading - Öz, Fatih Ertuğrul. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
In this study, a three-dimensional Representative Volume Element (RVE) with hexagonally packed array is used to predict the mechanical behaviour of a unidirectional carbon fibre reinforced epoxy under various types of loading. Firstly, elastic moduli, Poisson’s ratios, coefficients of thermal expansion (CTE) and shear moduli of a unidirectional carbon fibre reinforced polymer (CFRP) are predicted using proper boundary conditions under various types of loading in ABAQUS Finite Element Software. Secondly, Manufacturer’s Recommended Cure Cycle (MRCC) of AS4/8552 composite is modelled as a thermal loading process to calculate the micromechanical residual stresses developed during manufacturing. A user defined material subroutine (UMAT) is developed to model the incremental moduli as well as cure and thermal contraction of the resin as it cures. At the end of the cycle, it is observed that, most of the residual stresses are produced as a result of cooling from curing temperature to room temperature. Stress distributions in fibre-matrix interface at the end of the cycle are presented. Finally, progressive damage model is applied to assess the failure mechanisms of AS4/8552 under various types of loading. Maximum Principal Stress, Raghava’s and Bauwen’s modified von Misses failure criteria are applied with element stiffness reduction method. Resin-dominated strength values, cited in the manufacturer’s data sheet like transverse tensile strength, transverse compression and in-plane shear strength are successfully predicted by using the strength and stiffness values of constituent materials provided by the manufacturer. At the end of the analysis, it is found that, damage initiation and its evolution are highly affected by loading type, loading direction and residual stresses.
Keywords: Finite element method -- Mathematics.